OUTSTANDING SCHOLARS WHO CONTRIBUTED A LOT TO THE DEVELOPMENT OF UZBEK TRANSLATION (Proceedings of International Educators Conference, 2022)
This article presents the brief history and evolution of Translation Studiesfrom Uzbek into English. It also provides information about outstanding scholars who contributed to the development of Uzbek translation. Moreover, there are presented some possible lexical problems intranslation between Uzbek and English, and how to solve them. It providesexamples of such problems in translation and considers how to deal with them. Thearticle also discusses the lack of equivalence in translation, whichresults in lexical misunderstanding at the semantic field level.